Answer:
y= -x +2
Step-by-step explanation:
y-y1 = m(x-x1)
y - 0 = 1(x - (-2))
y = -x + 2)
y = x + 2.
Justin buys 4 hot dogs ad 5 pop corn boxes at the baseball game.
<h3>Equation</h3>
Equation is an expression which is used to show the relationship between two or more variables and numbers.
Let x represent the number of hot dogs and y represent the boxes of popcorn.
Justin buys a total of 9 snacks. Hence:
He buys popcorn 3 less than twice as many hot dogs. Hence:
Solving equations 1 and 2 simultaneously gives:
x = 4, y = 5
Justin buys 4 hot dogs ad 5 pop corn boxes at the baseball game.
Find out more on equation at: brainly.com/question/13763238
-5x = x + 6(1-x)
-5x = x + 6(1) + 6(-x)
-5x = x + 6 -6x
-5x = x - 6x + 6
-5x = -5x + 6
-5x + 5x = 6
0 = 6 Not equal. No solution.
(2x-5)² = (2x-1)(2x+1) -10(2x-1)
(2x-5)(2x-5) = (2x-1)(2x+1) - 20x + 10
2x(2x-5)-5(2x-5) = 2x(2x+1)-1(2x+1) - 20x + 10
4x² - 10x -10x + 25 = 4x² + 2x - 2x -1 - 20x + 10
4x² - 20x + 25 = 4x² - 20x - 1 + 10
4x² - 20x + 25 = 4x² - 20x - 9
Not equal. No solution.
Answer: I think it is the second choice. The others don't make sense
Step-by-step explanation: